Implementasi dan Pemasyarakatan Portal Akademik Berbasis Web di SD Negeri 060878 Sebagai Pendukung Efisiensi Layanan Pembelajaran untuk Admin, Guru, dan Siswa - Andysah Putera Utama Siahaan; Hafizhah Sufina Azzahra (LKP KARYA PRIMA KURSUS, 2025)
This community service activity was carried out at one of the partner schools with the aim of introducing and socializing the school academic portal as a digital platform for managing academic and administrative data. During this program, teachers and school staff were trained on how to use the portal, including login procedures, student data management, grading, and online academic reporting. The implementation methods included presentations, live demonstrations, and interactive Q&A sessions. This activity also served as a collaboration between the school and students of Universitas Pembangunan Panca Budi in applying information technology to the education sector. The results showed an increased understanding and interest among school staff in adopting a web-based academic information system to enhance the effectiveness and efficiency of school administration processes.